2004
DOI: 10.1002/art.11482
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma suppression of matrix metalloproteinase 1, but not interleukin‐6, through a p38‐dependent pathway in rheumatoid arthritis synovial fibroblasts

Abstract: Rb-mediated suppression of IL-6 and MMP-1 occurs at a posttranscriptional level. However, Ad-Rb reduction of MMP-1 but not IL-6 requires inhibition of the p38 pathway. These results suggest that Rb negatively regulates p38 activation, leading to decreased MMP-1 secretion in RA synovial fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 75 publications
1
10
0
1
Order By: Relevance
“…Combined use of conventional medication and smCDK inhibitors may well have a synergistic antiarthritic effect. As was revealed by our recent report and others (30,39,40), CDKI may have broader activity than anticipated. We found recently that both alvocidib and compound A suppressed matrix metalloproteinase-3 production by synovial fibroblasts and osteoclastogenesis of macrophages (data not shown).…”
Section: Discussionsupporting
confidence: 55%
“…Combined use of conventional medication and smCDK inhibitors may well have a synergistic antiarthritic effect. As was revealed by our recent report and others (30,39,40), CDKI may have broader activity than anticipated. We found recently that both alvocidib and compound A suppressed matrix metalloproteinase-3 production by synovial fibroblasts and osteoclastogenesis of macrophages (data not shown).…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, it has been reported that its direct inhibitor pRb is constitutively inactivated in RASF 19. In order to investigate whether the TNFα-induced expression of EZH2 might be due to the activation of E2F, we performed reporter gene assays with luciferase vectors containing the EZH2 promoter with the wildtype or a mutated binding site for E2F (figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been demonstrated that restoration of Rb to appropriate levels inhibits the cell cycle as well as down-regulates the production of IL-6 and MMP-1 in RASF [22].…”
Section: Cell Cycle Regulation and Oncogenesmentioning
confidence: 99%